Normative database of retinal nerve fiber layer and macular retinal thickness in a Thai population - Anita Manassakorn (2018)
Purpose: To investigate the distribution of retinal nerve fiber layer (RNFL) and macular retinal thickness measured by optical coherence tomography (OCT) in a Thai population. Methods: We studied one eye each of 250 healthy subjects [age ≥ 18 years; spherical refractive error within ±6 diopters (D); astigmatism ≤3 D; no ocular pathology]. A complete eye examination, standard automated perimetry, and fast RNFL and macular thickness measurement by OCT were performed, and a disc photograph was taken. The distributions of both thicknesses, including their relationship with demographic data, were analyzed. Results: The mean ± SD age of the study population was 44.7 ± 12.2 years. The mean ± SD RNFL thickness was 109.3 ± 10.5 m, which was 10% thicker than that in the OCT normative database. RNFL decreased 2.3 m per decade (P < 0.001). Sex and spherical equivalent were not associated with RNFL thinning. The mean ± SD central foveal thickness was 183.2 ± 1.3 m. The macular thickness in the outer area was significantly thinner than that in the inner area (P < 0.001). The temporal regions were the thinnest among the four quadrants (P < 0.001). Thinning of all macular areas, except the center, was found to be associated with advancing age (P < 0.05). Conclusions: RNFL thickness in the measured Thai population was about 10% thicker than that in the original normative database. Macular thickness and RNFL thickness in the superior and inferior quadrants decreased with advancing age. © 2008 Japanese Ophthalmological Society (JOS).